(untitled) (Bangladesh Journal of Botany, 2026)
The anatomical study of leaf of Monstera deliciosa Liebm. was performed commonly grown in Pakistan. The epiphytic species was collected from the trunk of Ficus bengalensis. The anatomical characters of the leaf were studied under the light microscope Transverse section of petiole consists of epidermis, thick cuticle, hypodermis, cortex, metaxylem, protoxylem and druses. Largest metaxylem (0.98±0.07) and protoxylem (0.75±0.07) were observed in the petiole. In mid vein upper and lower epidermis, sclerenchymatous hypodermis, metaxylem, protoxylem, phloem and needle-like crystals were observed. However, mesophyll cells, a large number of needle-like crystals, druses and vascular bundle were seen. Smallest metaxylem (0.60±0.03) and protoxylem (0.45±0.06) were observed in lamina. Anatomical features of epidermis include the brachyparahexacytic type stomata, kidney-shaped guard cells and irregular epidermal cells. Larger epidermal cells (19.36±0.80) were seen in the abaxial epidermis. So, it is concluded that this plant is adapted very well in epiphytic form and its fleshy stem help to survive in tropical areas. Bangladesh J. Bot. 55(1): 31-35, 2026 (March)